Islam and Economy: Towards a Just Islamization of Economics - Sirait, Frida Yanti (Universitas Muhammadiyah Sumatera Utara, 2025)
This study aims to explore the concept of the Islamization of economics, focusing on the integration of Islamic principles into the conventional economic system. It highlights the need for an ethical and value-based economic framework rooted in Islamic teachings. The research adopts a qualitative approach, using library research to review relevant literature on Islamic economics, the Islamization of knowledge, and the intersection between Islamic teachings and economic principlesThe study finds that Islamic economics offers an ethical and moral framework that emphasizes fairness, justice, and social welfare. It highlights the significance of integrating Islamic values such as the prohibition of interest (riba) and the promotion of zakat (charity) and profit-sharing mechanisms into the economic system. The research concludes that the Islamization of economics can lead to the development of a more inclusive and sustainable economic system that aligns with both Islamic and universal principles.